O "Spisovniku za Slovence" Matije Majarja - Hafner, Stanislav (Traditiones (Ljubljana), 1999)
In his Spisovnik (1850) Matija Majar-Ziljski, a connoisseur of Slovene folk narrative tradition, enriched Slovene linguistic didactics and literary tradition in the period of Slovene Romanticism by adopting its permanent short syntagmas
Keywords: Majar, Matija, 1809-1892; slovstvena folklora; ethnology; etnologija